Willingness of adolescent girls and young women to participate in future clinical trials of long-acting PrEP implants for HIV prevention, Kampala Uganda. - Jane Frances Lunkuse; Grace Godfrey Sseremba; Candice Chetty-Makkan; Elizabeth Wahome; Matt A Price; Yunia Mayanja (PLOS Global Public Health)
Adolescent girls and young women (AGYW) continue to face a significant risk of HIV infection, particularly as numerous experimental prevention products are in development. This study assessed the willingness to participate (WTP) in future clinical trials of long-acting HIV pre-exposure prophylaxis (PrEP) implants among AGYW at high risk of HIV infection in Kampala, Uganda. From January to October 2019, we conducted a cross-sectional study among AGYW aged 14-24 years. Interviewers _collected data on socio-demographics, substance use, sexual behavioural risk, contraceptive use and laboratory diagnosis of sexually transmitted infections (STIs). Participants were asked about their WTP in future clinical trials of a long-acting PrEP (LAP) implant. Multivariable logistic regression models were fitted to determine participant characteristics associated with WTP in future clinical trials of a PrEP implant. We enrolled 285 participants, with a median age of 20 years. Among them, 57.2% were single, 54.7% had completed at least secondary education, 92.6% engaged in transactional sex, 36.5% had multiple new male partners, 25.3% tested positive for STIs (chlamydia or gonorrhoea), and 15.4% reported drug use in the past three months. Nearly half (45.6%) of the AGYW expressed willingness to participate in a future HIV prevention study involving the LAP implant. Willingness to participate in a future HIV prevention study involving the LAP implant was higher among those with multiple new male partners (adjusted odds ratio [aOR] 1.84, 95%CI 1.09-3.11, P = 0.022) and those using contraceptives (aOR 1.69, 95% CI 1.00-2.85, P = 0.047) but lower among those with higher income levels (aOR 0.46, 95%CI 0.25-0.84, P = 0.013). These findings suggest that AGYW with higher HIV risk and those with prior contraceptive experience could potentially participate in future clinical trials of the LAP implant.